ANALISIS PEMBELAJARAN PENDIDIKAN KARAKTER DISIPLIN DI SD NEGERI NEGLA - Listin Lia; Cece Rakhmat; Fajar Nugraha (LPPM Universitas Perjuangan Tasikmalaya, 2021)
Abstract: This study aims to describe the profile of disciplinary character habituation and aspects of discipline character education for grade 5 at SDN Negla. This study used a qualitative descriptive approach with research subjects, namely grade 5 students at SDN Negla with data collection techniques in the form of interviews, observation, documentation, and questionnaires. The results showed that the profile of disciplinary character education habituation at SDN Negla has an average score of 54.9 (including the criteria,